Analisis Penulisan Surat Lamaran Pekerjaan Mahasiswa Semester II Tahun Akademik 2021/2022 Program Studi Administrasi Bisnis Politeknik Negeri Banjarmasin - sari hepy maharani; Tarman Effendi; Rika Novyanti (BIMA: Jurnal Bisnis dan Manajemen, 2023)
The study titled "Analysis of Writing Job Application Letters for Second Semester Student Academic Year 2021/2022 Business Administration Study Program Banjarmasin State Polytechnic" aims to (1) determine the writing of the opening part of the second semester student job application letter for the academic year 2021/2022 Business Administration Study Program Banjarmasin State Polytechnic, (2) determine the writing of the contents of the second semester student job application letter for the academic year 2021/2022 Business Administration Study Program Banjarmasin State Polytechnic, (3) determine the writing of the closing section of the second semester student job application letter for the Banjarmasin State Polytechnic Business Administration Study Program's 2021/2022 academic year. The descriptive method was used in this study. This study's sample size is 35 job application letters. The documentation study technique was used to collect data for this study. This study's data processing technique is the analysis of 35 job application letters for Banjarmasin State Polytechnic Business Administration Study Program second semester students in the 2021/2022 academic year. Data analysis, particularly data pertaining to job application letters, including (1) writing the opening section, (2) writing the content section, and (3) writing the closing section. Based on the analysis of writing job application letters for second semester students of the Banjarmasin State Polytechnic Study Program for the 2021/2022 academic year, it can be stated that (1) incorrect writing was found in the opening part of the second semester student job application letters for the 2021/2022 academic year of the State Polytechnic Business Administration Study Program Banjarmasin, both in the writing of attachments, pages, addresses, and greetings, but only a few of the incorrect writings were found, while the correct writings were more numerous, except for the writing of the date, no writing errors were found, (2) In the writing of the contents of the second semester student job application letter for the 2021/2022 academic year, the Banjarmasin State Polytechnic Business Administration Study Program still found errors in writing, both in the writing of the opening paragraph, body paragraph, and closing paragraph, but the number of incorrect writings was only a few, while full There are more correct verbal statements, and (3) in the writing of the closing part of the second semester student job application letter for the 2021/2022 academic year, the Banjarmasin State Polytechnic Business Administration Study Program still found incorrect writing, both in writing the closing greeting, signature, and applicant's name, but the number of incorrect writing is only a few, while the correct writing is more.